Diffuse large b cell lymphoma associated with unspecified Epstein Barr virus: review of the literature - Beltrán Gárate, Brady (2022)
Diffuse Large B-Cell Lymphoma associated with Epstein Barr virus Not otherwise specified is a frequent entity in South America, which affects patients of all ages but more frequently senile patients. Diagnosis is through the identification of the Epstein Barr virus within the tumor cell using the EBER test. The prognosis is unfavorable despite having improved with the introduction of rituximab. There are new prognostic scores for the identification of risk subgroups. The treatment continues to be the same as for cases of Epstein Barr virus-negative diffuse Large B-Cell Lymphoma. New novel therapeutic strategies against this entity are expected.